2022
DOI: 10.1186/s13059-022-02742-7
|View full text |Cite
|
Sign up to set email alerts
|

A pan-Zea genome map for enhancing maize improvement

Abstract: Background Maize (Zea mays L.) is at the vanguard facing the upcoming breeding challenges. However, both a super pan-genome for the Zea genus and a comprehensive genetic variation map for maize breeding are still lacking. Results Here, we construct an approximately 6.71-Gb pan-Zea genome that contains around 4.57-Gb non-B73 reference sequences from fragmented de novo assemblies of 721 pan-Zea individuals. We annotate a total of 58,944 pan-Zea genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 151 publications
0
32
0
1
Order By: Relevance
“…Recently, the ‘super‐pangenome’ (Khan et al., 2020), a broader level of pangenome that represents the genome of a genus, has stood out in crops for better leveraging the wild relatives in genomics‐assisted breeding. The super‐pangenomes of two main crops, rice and maize, have been released in 2022 (Gui et al., 2022; Shang et al., 2022). For the rice super‐pangenome, the authors have selected 251 rice accessions representing the genetic and phenotypic diversity of cultivated and wild rice germplasm, and the super‐pangenome was constructed based on the ONT sequences of these 251 accessions.…”
Section: Plant Pangenomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the ‘super‐pangenome’ (Khan et al., 2020), a broader level of pangenome that represents the genome of a genus, has stood out in crops for better leveraging the wild relatives in genomics‐assisted breeding. The super‐pangenomes of two main crops, rice and maize, have been released in 2022 (Gui et al., 2022; Shang et al., 2022). For the rice super‐pangenome, the authors have selected 251 rice accessions representing the genetic and phenotypic diversity of cultivated and wild rice germplasm, and the super‐pangenome was constructed based on the ONT sequences of these 251 accessions.…”
Section: Plant Pangenomesmentioning
confidence: 99%
“…Further analyses have highlighted the important effects of SVs on important agronomic traits (thousand‐grain weight and grain length) through altering gene expression levels. For the Zea super‐pangenome, the authors have constructed a pan‐ Zea genome of approximately 6.71 Gb using publicly available maize genome assemblies and de novo fragmental assemblies of 721 pan‐ Zea individuals (Gui et al., 2022). The authors have highlighted the potential value of this pan‐ Zea genome in maize breeding (introduced in more detail in the case studies section below).…”
Section: Plant Pangenomesmentioning
confidence: 99%
“…An effort to quantify SNP and transposon insertion diversity within an association panel used for genome‐wide association studies identified approximately 2.4 million SNPs and 0.45 million segregating transposon associations across a panel of approximately 500 temperate adapted maize lines (Qiu et al., 2021; Renk et al., 2021). Finally, a recent study of genus‐wide genetic variation in maize identified approximately 65 million SNPs and approximately 8 million InDels by generating sequencing data to an average depth of 22× from 239 accessions of wild relatives (Chen et al., 2022; Gui et al., 2022), in combination with the diversity panel of approximately 500 maize lines sequenced by Yang et al. (2019).…”
Section: Introductionmentioning
confidence: 99%
“…An effort to quantify SNP and transposon insertion diversity within an association panel used for genome wide association studies identified approximately 2.4 million SNPs and 0.45 million segregating transposon associations across a panel of approximately 500 temperate adapted maize lines (Qiu et al ., 2021; Renk et al ., 2021). Finally, a recent study of genus wide genetic variation in maize identified approximately 65 million SNPs and approximately 8 million InDels by generating 22x average depth sequencing data from 239 accessions of wild relatives (Chen et al ., 2022; Gui et al ., 2022) in combination with the approximately 500 entry maize diversity panel resequenced in (Yang et al ., 2019). The largest scale of these efforts to date is likely the aggregate analysis of 1,218 maize lines as part of the maize HapMap3 project representing global maize diversity, however, higher sequencing costs at the time of this study resulted in lines being resequenced to a median depth of 2x (Bukowski et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis of phenotypic and genetic changes associated with the breeding effort in different temperate breeding programs generated resequencing data from 350 maize inbreds from China (187) and the United States (163) sequenced to a median depth of 12x and identified more than 29 million genetic markers relative to the B73_RefGen_V3 reference genome (Wang et al, 2020). An effort to quantify SNP and transposon insertion diversity within an association panel used for genome wide association studies identified approximately 2.4 million SNPs and 0.45 million segregating transposon associations across a panel of approximately 500 temperate adapted maize lines (Qiu et al, 2021 (Chen et al, 2022;Gui et al, 2022) in combination with the approximately 500 entry maize diversity panel resequenced in (Yang et al, 2019). The largest scale of these efforts to date is likely the aggregate analysis of 1,218 maize lines as part of the maize HapMap3 project representing global maize diversity, however, higher sequencing costs at the time of this study resulted in lines being resequenced to a median depth of 2x (Bukowski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%